Instan Oyster Mushroom Instant Porridge for the Elderly - Faisal Akbar Zaenal; Syahrial Syahrial; Abdi Nurul Masyhar (Politeknik Pariwisata Makassar, 2022)
This research is an experimental study that aims to determine: (1) The process of making instant porridge substituted with oyster mushrooms; (2) Panelists' acceptance of the organoleptic test of instant porridge substituted with oyster mushrooms, which includes color, aroma, texture, taste, and overall (overall assessment); (3) Potassium Nutritional Value of oyster mushroom substituted porridge product. There were 38 panelists, consisting of 3 trained panelists, 25 semi-trained panelists, and 10 untrained panelists. The data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive analysis and the ANOVA test. The research was out at the Kitchen Laboratory and the Makassar Health Laboratory Center. The results showed that making oyster mushroom substitution slurry started from material preparation, weighing materials, cutting materials, grinding materials, drying materials, and storage. The panelists' acceptance of the oyster mushroom substitution porridge with the F1 formulation with a yield of 1.5 grams of dry oyster mushrooms is equivalent to 15 grams of fresh oyster mushrooms. In terms of assessment of color, aroma, texture, and taste, it is better than other formulations with a color rating of 4.18, aroma, texture, and taste of 4.82, and overall, 5.42. The change in the nutritional value of potassium in oyster mushroom instant porridge was 225.75 mcg, and the nutritional value of iron was 14.72 mcg.